Study and investigation into aspects of material recyclability - Lai, Xian Heng (Nanyang Technological University, 2021)
Advanced composites manufactured with glass and carbon-fibers are dominating leading markets in the aerospace, marine, automotive and sporting industries for decades. The exponential rise with their demand were attributed to their high strength and low weight properties. However, environmental concerns such as petroleum resources, waste disposal, high carbon emissions and expensive prices have promoted for more sustainable materials to be manufactured to replace synthetic composites. Sustainable materials like green composites that are made from natural fibers are bio-degradable, renewable, lighter and cheaper to manufacture. Coir fibers are used as a by-product replacement as a soil-less substrate for agricultural cultivation and various household applications. It is also known to have good toughness and impact properties because of its high strain to failure elongation rate which can be investigated after processing it into a composite. The low cost and wide availability of coir fibers as a natural fibers resource enables it to be explored towards manufacturing green composites. However, little research has been done to determine the mechanical properties from the hybridisation of coir composites with glass fibers as an additional reinforcement layer. The author would also study the benefits of the various orientation for coir fibers and glass fibers that are used as reinforcement layers for this research project. Furthermore, the arrangement in different orientation can greatly affect the overall performance of the green composite. Based on comparison to glass fibers composites, natural fibers composites are much weaker in strength. Hence, this research was based on manufacturing coir composites with glass fibers as the additional constituent to study and investigate its mechanical properties influence in composites. Coir fibers hybrid composites were also manufactured with glass fibers to study and to characterise the strengthening mechanical properties that it can provide coir fibers. The epoxy resin - EPICOTE 2009 was used in the fabrication process of the composites as the matrix because it is compatible with coir fibers and glass fibers. Four different combinations of composites laminates were fabricated for this research project with coir fibers in random orientation and, glass fibers in uniaxial and cross-ply orientation, respectively. Instrumented tests to assess the composite laminates mechanical properties were carried out with tensional test, flexural bending test, Izod impact and water absorption test. The obtained results from the conducted tests shows high mechanical properties for the coir hybrid composites processed with glass fibers oriented in the uniaxial direction. Hence with this derived improvement of material hybridisation of composites, it can potentially open more opportunities towards composite applications. It will path the way for manufacturing natural fibers material in an environmentally sustainable approach.